Reactivity of Joncryl chain extender in PLA/PBAT blends: Effects of processing temperature and PBAT aging on blend performance - Nofar, Mohammadreza; Jahani, Davoud; Özsaltık, Ceren; Altınbay, Aylin (Elsevier BV, 2025)
This study investigates the effects of incorporating an epoxy-based Joncryl chain extender on the reactivity and performance of amorphous polylactide/poly(butylene-adipate-co-terephthalate)(PLA/PBAT) blends processed at various temperatures. The impact of using freshly provided PBAT versus aged PBAT on Joncryl's reactivity and blend performance is also examined. Joncryl's interactions with PLA, PBAT, and their blends at different temperatures were assessed using rheological analysis. The blends morphology, tensile and impact properties, and dynamic mechanical analysis were examined. Increasing the processing temperature enhances Joncryl's reactivity with PLA more noticeably than that with PBAT but also accelerates PLA degradation. Although PBAT exhibits reactivity with Joncryl, aged PBAT with significantly suppressed melt rheological properties remained largely unaffected by the presence of Joncryl. Overall, the melt rheological properties of blends improved with Joncryl addition at higher processing temperatures, likely due to the increased Joncryl reactivity and enhanced compatibilization. The tensile properties of blends processed at higher temperatures are more adversely affected by bioplastic degradation, although Joncryl addition mitigates these effects. Impact strength increased with higher processing temperatures due to enhanced Joncryl reactivity, more effective interfacial compatibilization, and PBAT phase droplet refinement. Blends prepared with aged PBAT exhibited markedly poorer mechanical performance, attributed to severely suppressed melt properties and resultant non-homogeneous blend morphology.
Keywords: Polyesters; Tensile Strength; Temperature; Epoxy Compounds; Rheology